Maternal and perinatal outcome in placenta previa: an observational study at a tertiary care hospital in Mysore, Karnataka, India - Sorakayalapeta, Maunica Reddy; S. Manoli, Nandish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: 2-5% of the pregnancies are complicated by antepartum haemorrhage. About one third of them are due to placenta previa thus contributing to a significant amount of maternal and perinatal morbidity and mortality. In the present times with liberally increasing caesarean section rates, there is a changing trend in the incidence and complications of placenta previa. The objective of this study was to evaluate the obstetrical characteristics and maternal and perinatal outcome of cases of placenta previa. Methods: This was a prospective observational study conducted in the Department of Obstetrics and Gynaecology of JSS Medical College and Hospital, Mysore during the period January 2017 to June 2018. Results: Out of total 13,150 deliveries during this period, placenta previa was observed in 131 cases with an incidence of 1%. Majority belonged to the age group 25-29 years (48.8%). 66% of the cases presented with painless vaginal bleeding as their chief complaint. The major risk factor was previous caesarean delivery seen in 29.8% cases followed by history of abortion in 18.3%. 67% cases had major degree placenta previa. Remaining 33% cases had minor degree. One case was complicated by placenta accrete. Peripartum hysterectomy was performed in 3.1%. Preterm deliveries amounted to 29.8%. Maternal and perinatal mortality were 0.76% and 3.05% respectively. 10.7% cases had Postpartum haemorrhage and 3.8% required ICU admission. 25% neonates required NICU admissions and 10% had RDS. Conclusions: Placenta previa is a prime contributor to substantial maternal and perinatal morbidity and mortality. Early referral to tertiary care centres, anticipation of clinical complications and appropriate measures can avoid grave consequences. Such cases must always be managed at a higher centre with good NICU services and round the clock operation theatre and blood bank facility.